S128 Highly invasive capsular serotypes of Streptococcus pneumoniae bind high levels of Factor H and are resistant to complement and phagocytosis. (2nd December 2011) - Hyams, C; Trzcinski, K; Weinberger, D M; Lipsitch, M; Brown, J S
Abstract : The Streptococcus pneumoniae polysaccharide capsule is an essential virulence factor that varies in structure between serotypes. While certain serotypes are highly invasive, it is unknown why these serotypes frequently cause infection yet others generally cause nasopharyngeal colonisation. Complement is vital in immunity to pneumococcus, and the capsule is known to affect complement deposition. Activation of the alternative complement pathway is promoted by factor B (Bf) binding, but inhibited by factor H (FH) activation. We hypothesised that capsule effects on FH and Bf interactions could alter S pneumoniae complement sensitivity, partially explaining serotype-dependent differences in invasiveness. C3b/iC3b deposition, FH and Bf binding to S pneumoniae were measured using flow cytometry assays on 20 distinct capsule-switch variants constructed on TIGR4 genetic background. These strains were therefore identical in protein structure, differing only in capsular serotype. Phagocytosis was investigated using an established flow cytometry assay, fresh human neutrophils and FAMSE labelled S pneumoniae . FH binding showed wide variations between TIGR4-capsular switched strains, with a 7.5-fold difference between the highest (serotype2) and lowest (serotype11A) results. Differences in FH binding between strains did not correlate with capsular thickness, or with capsule structural motifs such as numbers of carbon atoms per repeating unit. FH binding negatively correlated with Bf binding and C3b/iC3b deposition, demonstrating that increased FH binding was associated with reduced alternative pathway activity and increased resistance to complement. IgG binding did not correlate with C3b/iC3b results, suggesting C3b deposition was independent of antibody-mediated complement activity. Neutrophil association correlated with C3b/iC3b deposition (R 2 =0.47, p=0.0008) but negatively with FH binding (R 2 =0.74, p<0.0001), confirming that high FH binding by pneumococcus was associated with reduced neutrophil phagocytosis. Weakly- and highly-invasive serotypes showed large significant differences between median C3b deposition (p=0.007), neutrophil association (p=0.0002) and FH binding (p=0.0005). Weakly-invasive serotypes had reduced FH binding, increased C3b/iC3b deposition and increased neutrophil association. Our novel finding that the degree of FH binding to S pneumoniae capsular serotypes is associated with large variations in virulence offers a mechanistic explanation as to why certain serotypes are more invasive than others. It also provides a potential in vitro method for identifying highly invasive strains.